Continued Exploration of Barley Genotype Contribution to Base Malt and Beer Flavor Through the Evaluation of Lines Sharing Maris Otter® Parentage. (4th July 2022) - Morrissy, Campbell P.; Féchir, Michael; Bettenhausen, Harmonie M.; Van Simaeys, Karli R.; Fisk, Scott; Hernandez, Javier; Mathias, Kyle; Benson, Amanda; Shellhammer, Thomas H.; Hayes, Patrick M.
Abstract: Heirloom barley ( Hordeum vulgare L. ) varieties remain interesting to maltsters and brewers for their perceived unique flavor contributions to beer, despite not meeting contemporary agronomic and malting expectations. This study utilized crosses of the heirloom Maris Otter® and two contemporary genotypes to determine if "updated heirlooms" could be produced that would show improved agronomics and contemporary malt quality, while contributing uniquely to malt and beer sensory and chemical profiles. Using a recently established pipeline of malting; brewing; hot steep and beer sensory; and metabolomics to evaluate barley genotype contributions to malt and beer flavor, four experimental lines were compared to a control. The experimental lines were also assessed for their genomic contribution from their respective parents to further elucidate regions of the Maris Otter genome that may contribute to unique beer flavors. Results show improved agronomic outcomes relative to the heirloom parent and were comparable to the control. Malting quality met current recommendations. However, sensory properties attributable to the unique heirloom parent were not found. Further, chemical profiling did not explain the observed nuanced sensory differences, nor did it reveal unique metabolites not described by the sensory panels. Supplemental data for this article is available online at at http://doi:10.1080/03610470.2021.1952509.